2015
DOI: 10.1111/jiec.12382
|View full text |Cite
|
Sign up to set email alerts
|

The Environmental Impact of Two Australian Rock Lobster Fishery Supply Chains under a Changing Climate

Abstract: Summary Understanding the potential future impacts of climate change along the supply chain for highly traded fisheries products can inform choices to enhance future global seafood security. We examine the supply chains of the Australian tropical rock lobster fishery (TRL) and southern rock lobster fishery (SRL), with similar destination markets but different catch methods and fishing communities. A boat‐to‐market analysis allows for comparison and illustration of the effects of single supply‐chain aspects. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 63 publications
(121 reference statements)
0
11
0
Order By: Relevance
“…8,62,63 In addition, shifts can cause indirect repercussions on the processing and supply-chain industries of the associated fisheries. 64 The degree of impacts on the fishery depend on the flexibility of the markets as well as on consumer preferences. Markets can become more volatile, an effect that could magnify as resources decrease.…”
Section: Llmentioning
confidence: 99%
“…8,62,63 In addition, shifts can cause indirect repercussions on the processing and supply-chain industries of the associated fisheries. 64 The degree of impacts on the fishery depend on the flexibility of the markets as well as on consumer preferences. Markets can become more volatile, an effect that could magnify as resources decrease.…”
Section: Llmentioning
confidence: 99%
“…For aquaculture, the type and amount of feed is an important consideration, given the production of feed ingredients often dominates LCA results (see, e.g., [26,27]). In addition to the sustainability of production, the product yield and post-harvest losses can influence the sustainability of products [21] as can the mode of transport and energy source used for processing [28,29]. Seafood LCAs have predominantly addressed global-scale abiotic resource use and emission-based environmental impacts, such as global warming, toxicity and eutrophication [20].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have identified the need to build resilience to changing climate as an increasingly important challenge to supply chains (Levermann, 2014;van Putten et al, 2016;Lim-Camacho et al, 2017). COVID-19 has confronted supply chains with similar disruptions to transport and markets as climate change is predicted to do, and hence we have applied the same method to analyze the connectivity of supply chains and to identify the key agents in these chains which may be fragile and hence in need of focused attention.…”
Section: Discussionmentioning
confidence: 99%